Kinematical analysis of female volleyball spike - Chen, Y.-C.; Huang, C. F. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to analyze female volleyball players' body centre of mass (CM) displacement and velocity when spiking at front and back row. Six high school players participated in this study. Two JVC9800 digital video cameras (120Hz) were used to collect spiking motion. Kwon 3D motion system was used to analyze the kinematic variables. The results indicated that the back-row spike had greater CM resultant velocity at approach and take-off than front-row spike. The back-row spike had greater jumping height and the CM horizontal displacement than front-row spike. The initial ball velocity and angular velocity of shoulder, elbow, and wrist of the front-row spike were greater than back-row spike. This study provides information for coaches in teaching volleyball spike.